2015
DOI: 10.1007/s10529-015-1850-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic variation between different Chinese hamster ovary cell lines

Abstract: Certain transcripts can be used as markers for the identification of a CHO cell line undergoing recombinant development and thus represent a powerful tool for ensuring the maintenance of high quality standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A recent paper presented images of single karyotypes derived from metaphase spreads prepared with cells of five CHO host cell lines (two K1-derived, two DUXB11-and one DG44-derived cell population) [17]. The authors found these cell lines showing a large diversity of genotypes (pseudo-diploid, pseudo triploid, mixed pseudo diploid and triploid) with highly variable chromosomal structures.…”
Section: Chromosomal and Genomic Heterogeneity Of Cho Cells Other Cementioning
confidence: 99%
“…A recent paper presented images of single karyotypes derived from metaphase spreads prepared with cells of five CHO host cell lines (two K1-derived, two DUXB11-and one DG44-derived cell population) [17]. The authors found these cell lines showing a large diversity of genotypes (pseudo-diploid, pseudo triploid, mixed pseudo diploid and triploid) with highly variable chromosomal structures.…”
Section: Chromosomal and Genomic Heterogeneity Of Cho Cells Other Cementioning
confidence: 99%
“…Transcriptomics involves the analysis of gene expression levels under different conditions in an effort to reveal cellular mechanisms, response to environmental changes, treatments, and mechanisms of action. Applications in CHO bioprocessing include identification of cellular pathways and responses to varying conditions in order to optimize productivity and therapeutic product quality …”
Section: Transcriptomicsmentioning
confidence: 99%
“…Using Roche 454 sequencing technology and the Newbler Assembler, Becker et al assembled 1.84 million reads of several CHO cell lines and reconstructed metabolic pathways of the central carbohydrate metabolism and biosynthesis routes of sugars used for protein N‐glycosylation, enabling targeted pathway engineering for improved bioprocess characteristics . While Blas et al identified cell line specific markers by microarrays with the aim to use the markers in cell line development, Vishwanathan et al used RNA‐Seq data from 6 CHO cell lines and constructed microarrays to identify major functional pathways. The information gathered around variability with regard to growth, metabolism, and product consistency could be used for cell line engineering .…”
Section: Transcriptomicsmentioning
confidence: 99%
See 1 more Smart Citation